Analysis Of Financial Planning On The Sustainability Of Msme Businesses - Rahmi, Rahmi; Sultan Sarda; Masrullah, Masrullah (International Journal of Economic Research and Financial Accounting, 2024)
The purpose of this study is a type of quantitative research with the aim of determining the influence of financial planning in maintaining the sustainability of the MSME business in Makassar City. This sampling uses random sampling techniques from MSME actors in Makassar City who meet the criteria we determine. The type of data used in this study is quantitative data obtained from questionnaires that are shared and have a relationship with the problem under study. Data collection was carried out by observation, interviews and distribution of questionnaires. In this study, the data axis used in data collection includes primary data and secondary data. The research instrument used in this study is the Likert scale. Based on the results of data research using statistical calculations through the Statistical Package for the Social Science (SPSS) version 22 application regarding the influence of financial planning in maintaining the business continuity of MSMEs in Makassar City, the author draws a conclusion that financial planning has a positive and significant influence on business continuity. Good financial planning will influence MSME players in running their businesses and opening new branches.